Penyuluhan Hukum Pidana Bagi Petani Sawit Tentang Pengelolaan Limbah Perkebunan Yang Sesuai Hukum di Nagori Rabuhit Kecamatan Gunung Maligas Kabupaten Simalungun - Warsiman, Warsiman; Hikmatiar Harahap; M. Fauzi; Darmawan Yusuf; Irwansyah Tanjung; Apri Amalia (Institut Nalanda, 2026)
Improper management of oil palm plantation waste has the potential to cause environmental pollution and legal violations. Limited awareness and understanding among farmers regarding the legal aspects of waste management remain one of the factors affecting compliance with environmental regulations. This Community Service Program (PkM) aimed to enhance the legal awareness and understanding of oil palm farmers regarding lawful plantation waste management in Nagori Rabuhit, Gunung Maligas District, Simalungun Regency. The program employed an educational and participatory approach through legal counseling, interactive discussions, and question-and-answer sessions. The materials presented covered environmental law regulations, plantation waste management practices, and criminal sanctions for environmental violations. The results indicated an improvement in participants’ understanding of plantation waste types, the impacts of environmental pollution, and legal obligations related to waste management. Furthermore, the program increased farmers’ awareness of implementing responsible and environmentally friendly waste management practices. Legal counseling proved to be an effective preventive measure in supporting environmental protection and the sustainability of smallholder oil palm plantations.